Estimasi Resistivitas Tanah Menggunakan Komputasi Interpolasi Linear untuk Perancangan Sistem Pembumian di Kawasan Vulkanik - Rendi Rendi; Bragas Afrizaldhi Pratama; Nadya Glaudira (Fakultas Teknik Universitas Garut, 2026)
Accurate estimation of soil resistivity is crucial in the design of grounding systems, yet it is often constrained by the lack of data at specific depths (blind spot). This study aims to validate a MATLAB-based linear interpolation computational method for estimating soil resistivity in blind spot areas. For validation purposes, secondary data from the study by Rukmana et al. in a volcanic area at depths of 0.5 meters and 1.5 meters were used to predict the value at 1.0 meter, wichspre was then comparatively tested against the actual field data. Computational results show that the estimated values range from 13.105 Ωm to 19.965 Ωm. Relative error analysis demonstrates varying accuracy levels, with the smallest deviation of 4.42% in linear trends and the largest at 26.99% due to volcanic soil moisture anomalies. Technically, these resistivity values meet the safety limits of the General Requirements for Electrical Installations (PUIL) 2020 standard. Based on this testing, the linear interpolation method proves to be sufficiently representative for preliminary design estimation. It is recommended to use a single rod electrode configuration at the location without the need for additional additive engineering.